Children with Standard Risk Acute Lymphoblastic Leukemia in Induction And Consolidation Phase - Amarullah, Adinugraha; Hasmono, Didik; Ugrasena, IGD; Yulistiani, Yulistiani (Folia Medica Indonesiana, 2018)
Prednisone has an important role in the therapy of patient with standard risk ALL. Patients with standard risk ALL receiving high dose prednisone as therapy and supraphysiology dose of prednisone are expected to cause suppression in HPA-axis (Hypothalamic Pituitary Adrenal axis). This suppression could reduce immune system in children with ALL and increase infection risk because reduction of cortisol level. In Indonesia, we did not find study about the incident of adrenal suppression after high dose prednisone therapy, especially in induction to consolidation phase ALL patient. The aim of this study was to analyze adrenal suppression after high dose prednisone therapy on children with standard risk acute lymphoblastic leukemia in induction and consolidation phase. This study has received a certificate of Ethical Clearance No. 588/Panke.KKE/X/2016, a longitudinal observational, prospective, non-randomized trial involving children with ALL who received prednisone for 49 days during the induction phase. We collected and compared laboratory result of cortisol level in children with ALL and received prednisone therapy during induction to consolidation phase. Sample was taken at week 0,4,5,6,7,8,10,12 in the course of ALL chemotheraphy Indonesian protocol year 2013. Serum was examined using methods CLIA ADVIA Centaur® XP. Between June 2016 – January 2017, 13 patients (8 males, 5 females) were included in this study. Decrease of cortisol level after prednisone therapy occured in week-10 as much as 53% compared with week-0 (p=0.027). Cortisol level increased 64% of week-12 compared with week-10 (p=0.003). In conclusion, high dose prednisone is not significant to causing adrenal suppression in induction phase of ALL patients, and the reducing cortisol level is reversible.